Transition-Metal-Containing Bifunctional Catalysts (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue is dedicated to transition-metal-containing bifunctional catalysts, their design, and catalytic applications. Transition-metal-catalyzed reactions are highly demanded in modern chemical industry. Nanosized mono- and bimetallic particles as well as complexes of transition metals are well known as catalysts for many processes, such as hydrogenation, oxidation, deoxygenation, carbonylation, cross-coupling, etc. The search for novel supports is of high importance, and the optimization of catalysts’ morphology and functionalities is a constantly developing field. The Special Issue is focused on bifunctional catalysts, which is an emerging field of catalysis including a variety of systems: bimetallic, magnetically separable, inorganic (oxidic and carbonaceous), and polymeric systems.